IMPLEMENTATION OF THE RANDOM FOREST ALGORITHM IN CLASSIFYING THE ACCURACY OF GRADUATION TIME FOR COMPUTER ENGINEERING STUDENTS AT DIAN NUSWANTORO UNIVERSITY - Devi Ayu Rachmawati; Nitho Alif Ibadurrahman; Junta Zeniarja; Novi Hendriyanto (Jurnal Teknik Informatika (Jutif), 2023)
To ensure the existence of a university remains intact, one way that can be done is by optimizing the performance of the students so that they can graduate on time. A high percentage of on-time graduation will result in a good assessment of the accreditation of the department in the university. However, there are many factors that affect the graduation rate, such as the student's academic performance, extracurricular activities, and other factors. The data of graduation of students in the Computer Science program at the Faculty of Computer Science, Dian Nuswantoro University, for the academic years 2008-2017 is the object of this study. The objective of this research is to create the best classification model using the Random Forest algorithm to predict the accuracy of the graduation time of students, which will be useful for policy making in the future. The results of the classification using this algorithm received an accuracy of 93% for the training data and 91% for the test data.